Pendidikan Keluarga dalam Pasal 77-80 Kompilasi Hukum Islam (KHI) Perspektif Qira’ah Mubadalah - Kummala Ahmad SN, Lintang (Kartika: Jurnal Studi Keislaman, 2025)
Family education is often conceptualized as a model of parental education towards children. In the Compilation of Islamic Law (KHI), family education is conceived in two dimensions: the relationship between parents and children in the educational process, and the educational relationship between husband and wife. However, the latter tends to marginalize the position of women or wives. This study aims to reconstruct the concept of family education as stated in articels 77-80 of the Compilation of Islamic Law (KHI). This is a qualitative library research that employs legal tezt analysis through the qira’ah mubadalah perspective as the main analytical framework. The study reveals two key points. First, the mubadalah reading of article 80 (3) of th KHI transforms the one-directional concept of educating into a reciprocal relationship of mutual education. Second, mubdalah analysis of the adafe ‘al-ummahatu madrasatul ula’ reinforces the implementation of Article 77 (3) of the KHI by proposing a collaborativ co-parenting model. The implication is that this research contributes theologically and juridically to a more progressive interpretation of the KHI, while offering a collaborative and equitable model of family educatin between husband and wife within the father-mother relationship.